A Pilot Study on Acupuncture Clinic at Special Treatment Unit in Siddha Base Hospital Vavuniya - Saraswathy, P. (University of Jaffna, 2022)
Acupuncture is one of the traditional medicines. Acupuncture point correlated with varmam points in siddha medicine. Acupuncture is modified version of "Varmam therapy". The special treatment unit is functioning at base siddha hospital Vavuniya. In introduced acupuncture clinic in 2016. This is the pioneer of activity and pilot study clinic of acupuncture. Main objectivities of acupuncture clinic have been linked with the problem Statement. Significance analyzes in the curative service of the patients. The study analyzes the effects based on curative patients' records have been supported strongly by author who investigated the findings in relation to acupuncture clinic on special treatment unit. The literature highly supports. The designed methodology intends a survey of acupuncture clinic. Research period was 2years (2017-2018) observation research tool applied. Patient details and observation are recorded with the assistance of clinic patients and staffs. A Systematic random Sample of 2967 patients was selected from acupuncture clinic. Data were collected from the patient's records and analysis with SPSS26.Descriptive Statistics as gender, males -1080 female — 1887, age group and no of patient ratio 0-09:15, 10-19:30,20-29:438, 30-39:95, 40-49:1132, 50-59:95, 60-69:1140, 70-79:19, 80-89:03 Initial stage (1-7attempts) curative % of patients (CPP) 55%, Middle stage (7-14) (CPP) 30% above both are short term treatment. Final stage (more than 14) CPP is 15%. treated symptoms respectively in order relieving pain in Knee joint, Neck, Shoulder, lower limb, Wrist, Muscle, Multiple joint pain, Pain in upper limb, elbow joint pain, Ankle, weakness of upper limb and Swelling of leg. Treated Common aliments were diabetic neuritis, sciatica, hemiplegia, carpal tunnel syndrome, Arthritics, foot sprain and neuritis. Overall strategies, challenges are notified. Managerial benefits are implementing wide area, sustaining patients, full fill patient need and expectation and transform ancient text practical version. Correlation analysis, scatter plot resulted relationship. Acupuncture is effective for various illness. Especially vaatha noikal and older. This clinic is adoptable one in government, indigenous sector.
Keywords: Siddha Medicine; Acupuncture Clinic; Varmam; Vaatha noikal